PROPIEDAD VERSUS ADMINISTRACIÓN EN LAS ASOCIACIONES COOPERATIVAS - Fernández, Flory (1995)
This article studies Cooperatives as particular organizations in the capitalist context. Analyses part of the admínistrative structures, such as Vigilance Committe, which performes a fundamental role, in the attempt to establisb attachments between proprietaries and the administration of their property.